ANALISIS EFISIENSI FAKTOR PRODUKSI KARET DI KABUPATEN KAMPAR PROVINSI RIAU - Heriyanto Heriyanto; Darus Darus (DINAMIKA PERTANIAN, 2017)
Kampar regency is one of the districts in Riau province which contributes significantly to the economy in Riau Province, especially in the agricultural sector in the plantation sector. Rubber is a leading commodity in the plantation subsector that continues to be the government's attention to develop. Rubber plantations have important roles and positions, both economically, socially, absorbing labor and ecological roles. Plantation is also a source of prosperity, progress, independence, and pride of Kampar district government. Plantation management at present still relies on and relies on the abundance of human resources are relatively cheap. Efficiency, productivity, quality, sustainability are still low. Rubber farmers are generally less aware of how to use efficient production factors to obtain high rubber yields. The accuracy of the use of production inputs is important for farmers to achieve production efficiency levels both technically, allocatively and economically. This study aims to analyze the efficiency of rubber production in Kampar regency by building multiple linear regression model and production efficiency analysis. The results showed that the dominant factors affecting rubber production in Kampar Regency were number of plants, plant age, number of labor and investment. The factors of production are the number of plants, and the amount of labor is not technically efficient, allocative, and economical. The use of fertilizers tends to be technically and economically efficient, but alocatively inefficient. In order to obtain optimal production, this study recommends the need for rejuvenation of old or damaged rubber plants using superior seeds and maintained in accordance with the standards of rubber cultivation techniques. The efficient use of labor can be achieved by applying a rubber tapping system appropriately tailored to the conditions of the plant and the price of rubber. In addition, the use of balanced fertilizers (elements N, P, and K) in accordance with the recommended should be applied. Meanwhile, considering the fluctuating rubber prices and tend to vary between farmers, government intervention is required by applying a fair rubber auction market. Besides, there is an effort from farmers to maintain the quality of processed rubber